1998
DOI: 10.1021/ma9808169
|View full text |Cite
|
Sign up to set email alerts
|

Two-Component Gelators and Nucleating Agents for Polypropylene Based upon Supramolecular Assembly

Abstract: The supramolecular assembly of octyl-, hexadecyl-, and benzyl-substituted complementary tectonics based upon barbiturates (BA) and 2,4,6-triaminopyrimidines (TP) were studied in bulk, in cyclohexane, and in a polypropylene matrix. As evidenced by means of wide-angle X-ray scattering, FTIR spectroscopy, and atomic force microscopy (AFM), BA/TP assembly led to the formation of nanofibrillated superstructures, whereas the individual BA and TP components exhibited layered superstructures. Nanostructure formation r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 31 publications
1
44
0
Order By: Relevance
“…[4] Shinkai and co-workers have also made use of barbiturate derivatives to generate two-component gels.…”
Section: Two-component Organogelatorsmentioning
confidence: 99%
“…[4] Shinkai and co-workers have also made use of barbiturate derivatives to generate two-component gels.…”
Section: Two-component Organogelatorsmentioning
confidence: 99%
“…They are commonly used in the polymer industry to shorten injection‐molding cycle times, thus reducing production costs, generating smaller spherulites, and thus improving the optical and mechanical properties, as is the case for iPP 11. A large number of compounds were reported to nucleate the α form of iPP,10–14 and several others act as nucleating agents of the β form,15–27 depending on the dispersion and concentration of the additives and the cooling rates.…”
Section: Introductionmentioning
confidence: 99%
“…Higher T m , ΔH, and lower ΔS values suggested that the GG organogels were more stable than the MG organogels. [37,38] Addition of drug did not cause any significant variation in the thermal properties of both the types of organogels.…”
Section: Thermal Analysismentioning
confidence: 92%